Driving factors of carbon dioxide emissions and the impact from Kyoto protocol - Nicole Grunewald; Inmaculada Martínez-Zarzoso (Center for Economic Studies and ifo Institute (CESifo), 2009)
In the last two decades increasing attention has been paid to the relationship between environmental degradation and economic development. According to the Environmental Kuznets Curve (EKC) hypothesis this relationship may be described by an inverted-U curve. However, recent evidence rejects the EKC hypothesis for GHG emissions in a broad sense. In this paper we aim to investigate whether the EKC behavior for CO2 emissions could be proved on the behalf of institutional regulations. We analyze the driving factors of CO2 for developed and developing countries to test the theory of the EKC in the context of environmental regulations using a static and dynamic panel data model. We consider the Kyoto Protocol and the Clean Development Mechanism (CDM). The results from this study indicate that the Kyoto obligations have a reducing effect on CO2 emissions in developed and developing countries.
Keywords: Q54; Q56; 330; environmental Kuznets Curve; Kyoto Protocol; CDM; Environmental Kuznets Curve; Kohlendioxid; Luftverunreinigung; Klimaschutz; Umweltabkommen; Clean Development Mechanism; Industriestaaten; Entwicklungsländer